2021
DOI: 10.1128/mbio.03162-20
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Is Associated with Idiopathic Cutaneous Ulcers in Children on a Yaws-Endemic Island

Abstract: Exudative cutaneous ulcers (CU) in yaws-endemic areas are associated with Treponema pallidum subsp. pertenue (TP) and Haemophilus ducreyi (HD), but one-third of CU cases are idiopathic (IU). Using mass drug administration (MDA) of azithromycin, a yaws eradication campaign on Lihir Island in Papua New Guinea reduced but failed to eradicate yaws; IU rates remained constant throughout the campaign. To identify potential etiologies of IU, we obtained swabs of CU lesions (n = 279) and of the skin of asymptomatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…pertenue to penicillin and azithromycin resistance rates are low) [ 16 ]. This may be due to the fact that some yaws-like lesions may have a more complex aetiology, and resistance to treatment can be explained by the presence of other etiological factors, including Haemophilus ducreyi [ 2 ], Streptococcus pyogenes [ 17 ] as well as pathogens responsible for cutaneous leishmaniosis [ 18 ], leprosy [ 18 ] or Buruli ulcer [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…pertenue to penicillin and azithromycin resistance rates are low) [ 16 ]. This may be due to the fact that some yaws-like lesions may have a more complex aetiology, and resistance to treatment can be explained by the presence of other etiological factors, including Haemophilus ducreyi [ 2 ], Streptococcus pyogenes [ 17 ] as well as pathogens responsible for cutaneous leishmaniosis [ 18 ], leprosy [ 18 ] or Buruli ulcer [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 16S rRNA gene sequencing can skew bacterial abundance, can only detect bacteria that retain sufficient homology to the degenerate PCR primers employed, and cannot detect other types of microorganisms [12]. As well, S. pyogenes was not detected in over half of the IU specimens [5]. Thus, although both studies suggested that bacterial pathogens were associated with IU, they were limited by their inability to detect a broad range of microorganisms and failed to identify IU associated microorganisms in many IU specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical management of CU and future eradication efforts would be greatly improved by identifying all causes of CU in endemic communities. Here, we applied shotgun metagenomic sequencing to detect a broader range of microorganisms in the same CU samples prospectively collected 36, 42, and 48 months post-MDA from the Lihir Island cohort that we had analyzed by 16S rRNA gene sequencing previously [5]. Our goals were to confirm that S. pyogenes is associated with IU and to identify other possible bacterial and non-bacterial agents of IU.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations